Peace journeys: a new direction in religious tourism and pilgrimage research - McIntosh, Ian; Haddad, Nour Farra; Farra-Haddad, Nour; Munro, Dane (Cambridge Scholars Publishing, 2020)
To the top together : pilgrimage and peace-building on Sri Lanka's holy mountain / Ian S. McIntosh, Polgaswatte Paramananda -- From the north caucasus to Mecca and back : an unanticipated journey to tolerance / Mikhail A. Alexeev, Sufian N. Zhemukhov -- Shared pilgrimages : the potential of natural dialogue for religious tourism in Lebanon / Nour Farra Haddad -- The ritual efficacy of Baraka : healing of illness and its "side effects" for interethnic relations in Syria and Lebanon / Gebhard Fartacek, Lorenz Nigst -- Interfaith tourism in Ethiopia : an opportunity for socio-economic development and peace-building? / Senbeto Dagnachew -- "Settler-aware" pilgrimage and reconciliation : the treaty four Canadian context / Matthew R. Anderson -- Walking together : the Camino de Santiago pilgrimage as postsecular sanctuary / Douglas F. Challenger -- Building community through pilgrimage : the Pandhapur Vari pilgrimage in Maharashtra, India / Varada Sambhus -- Ziarah (pilgrimage) and the legacy of coexistence in Indonesia / Pierre Fournie -- Building a more sensitive world through religious tourism / Veena Sharma -- The pilgrimage into witness consciousness : towards healing and humanness / Roy Tamashiro -- Cultivating nonviolence : micro-pilgrimage as a pathway to peace / Alison T. Smith -- Finding inner peace on Spain's Camino de Santiago : an empirical study of pilgrim life stories / Christian Kurrat -- A Pauline progress : Protestant post-pilgrimage reflections / Dane Munro -- Pilgrimage as empowerment : women trailblazers / Janice Farley.